Territorialities and hydrocarbon policies. The case of coopertei and naval workshop (1991-2015) - Nahuel Mamonde (Boletín Geográfico)
In the Greater La Plata region, there are more than twenty work ventures formed by former workers of Yacimientos Petrolíferos Fiscales (YPF) who are providing different types of services to La Plata Industrial Complex. They emerged since 1991 because of the restructuring of the Refinery and their links have been modified in different contexts, which can be understood from a relational perspective as the result of the characteristics of the neoliberal accumulation regime and the neodevelopmentalist accumulation regime in Argentina. The methodology adopted is the intrinsic case study: it is the case in itself that interests, the one that once defined "... concentrates all the investigative attention oriented to an intense analysis of its meanings with the intention of understanding it in its specificity more than looking for generalizations "(Marradi, Archenti & Piovani, 2007: 238). The research is structured in three parts: in the first instance, the theoretical approach of the work is proposed, in a second, the aforementioned accumulation regimes are characterized and in a third, the case studies.